Dual role of Psudoalteromonas piscicida biofilm for the corrosion and inhibition of carbon steel in artificial seawater. (15th May 2019) - Moradi, Masoumeh; Ye, Sai; Song, Zhenlun
Highlights: Hydrodynamic conditions determine the corrosion influence of P. piscicida biofilm. P. piscicida biofilm covered the surface uniformly in orbital shaking conditions. In flat plate bioreactor, mushroom-like biofilms increased the corrosion rate. Farnesol as a QS inhibitor had different behavior in two hydrodynamic conditions. Hydrodynamic conditions changed the gene regulation of biofilm. Abstract: The role of Psudoalteromonas piscicida biofilm structures on the corrosion behavior of carbon steel was studied under two different hydrodynamic conditions, namely, orbital shaking incubator and flat plate bioreactor. Results showed a high number of wide and deep cracks on the metal surfaces exposed to flat plate bioreactor. On the contrary, the corrosion rate of carbon steel decreased and reached to its lowest value after two weeks of inoculation under orbital shaking condition. Different biofilm structures in both hydrodynamic conditions were observed through surface analysis. Adding farnesol as biofilm inhibitor exhibited different effect on the hydrodynamic conditions on biofilm structure.